Inner contrast and perceptual quality in tasks with video display units - O´donell, Beatriz Maria (2001)
The purpose of this paper is to find the physical luminance contrast of an image that best relates to perceptual quality in VDU achromatic tasks. The studies were carried out by measurement of visual performance, comfort judgements and contrast adjustment, taking into account different resolutions, polarities, background luminances and illuminance values. The results add a new piece of evidence about inner contrast as an appropriate criterion to describe perceptual contrast. Inner contrast also provides a satisfactory criterion for the optimum relation of luminances in inner details of characters. This paper shows that when the relation between suprathreshold perceptual response and stimulus magnitude - inner contrast - is plotted, the power function relationship is a curve that is concave downward; there is a compression of the perceptual response. Illuminance on the horizontal plane, within the experimental range (480 and 930 lux) is not a significant parameter. Background luminance is significant for comfort judgements and contrast adjustment trials, but not for visual performance results. Grey background and characters brighter than background seem to be preferred by the observers. Mean luminance contrasts higher than 5 are sufficient to reach a visual performance of 90% and good visual comfort. The corresponding inner contrast is 1.4.